Konzeptionelle Lehren aus der ersten Evaluationsrunde der~Branchenmindestlöhne in Deutschland - Bernd Fitzenberger; Annabelle Doerr (Journal for Labour Market Research, 2016)
– This paper provides a summary and a critical assessment of the evaluation studies on sectoral minimum wages in Germany, which were commissioned by the Federal Ministry of Labour and Social Affairs (BMAS). The evaluation of sectoral minimum wages is an important and successful example for the move towards evidence-based economic policy. All evaluation studies share the difficulty to identify the employees in the sectors which were actually covered by the sector specific minimum wage. We provide a critical discussion of the identifying assumptions, of the implementation of the difference-in-differences estimator, and of the choice of control groups. We discuss some alternative methodological approaches. We think that it would have been useful to analyze further the heterogeneity of the effect estimates and the choice of appropriate control groups. Furthermore, it would have been useful to assess the likely bias of the estimated effects.
Keywords: 330; Mindestlohn; Wirkungsforschung; Forschungsmethode; Ökonometrie; Kausalanalyse; Baugewerbe; Dachdecker; Gebäudereiniger; Wäscherei; Abfallwirtschaft; Pflegeberufe